2015
DOI: 10.1049/iet-map.2013.0624
|View full text |Cite
|
Sign up to set email alerts
|

Efficient iterative solution of electromagnetic scattering using adaptive cross approximation enhanced characteristic basis function method

Abstract: A new hybrid adaptive cross approximation-characteristic basis function method (ACA-CBFM) is proposed to efficiently solve the electromagnetic scattering problems. In the conventional ACA-CBFM, the ACA is only applied to speed up the construction of the reduced matrix that is directly solved and stored. However, with the increase of the size of the targets under analysis, the reduced matrix will become so large that it is difficult to directly solve and store. In this study, the reduced matrix is further compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…(5) can be efficiently calculated by many fast techniques [10,11,12]. Finally, after generating the reduced matrix equation, the coefficients of the CBFs can be directly solved by using the LU decomposition to the reduced matrix Z R .…”
Section: Characteristic Basis Function Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(5) can be efficiently calculated by many fast techniques [10,11,12]. Finally, after generating the reduced matrix equation, the coefficients of the CBFs can be directly solved by using the LU decomposition to the reduced matrix Z R .…”
Section: Characteristic Basis Function Methodsmentioning
confidence: 99%
“…The main computational cost of the CBFM consists of two parts: (1) the generation of the reduced matrix; (2) the LU solution of the reduced matrix equation. The cost of the reduced matrix generation have been successfully alleviated by many techniques [9,10,11,12,13]. Theses methods greatly enhance the efficiency of the reduced matrix filling.…”
Section: Introductionmentioning
confidence: 99%
“…The details of generating the CBFs are omitted, which can be found in [18], [25], and [26]. Assuming that the CBFs have been generated, the interactions Z R i,j between the CBFs in a far-block pair (i, j) at level l can be expressed as…”
Section: Mlfaca-cbfmmentioning
confidence: 99%
“…Nevertheless, in the hybrid ACA-CBFM, the reduced matrix is not compressed, which is directly stored and solved by a conventional direct approach. In [26] and [29], the authors have shown the compressibility of the reduced submatrix Z R i,j between well-separated high-level blocks, and use the ACA [11] or the ACA-SVD [17] to compress Z R i,j after it is generated. However, the generation of Z R i,j is very time consuming for large blocks.…”
Section: Mlfaca-cbfmmentioning
confidence: 99%
“…In recent years, several schemes have been proposed to accelerate the CBFs generation 8‐16 . One of them is to bypass the solution of dense matrices with a high‐frequency asymptotic technique, such as physical optics, 8,9 and with a multilevel approach by partitioning the spectrum of the incident plane waves 10 or partitioning the large blocks 11 .…”
Section: Introductionmentioning
confidence: 99%